The Influence of Competence and Work Motivation on Teacher Work Productivity Through the Work Environment at SMAN 51 Jakarta - Sugiyanto, Sundarwati; Pasaribu, Bomer; Samosir , Partogi Saoloan (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to examine the effect of competence and work motivation on teacher’s work productivity through the work environment. This research was conducted at SMAN 51 Jakarta with a total population of 75 teachers. The sampling technique in this study used purposive sampling, with the criteria of being teachers at SMAN 51 Jakarta. So this study used a sample of 75 teachers. This study used a quantitative method by distributing questionnaires to SMAN 51 and taking a number of books, journals, and examples of previous studies related to this research. Data analysis methods used in this research are regression analysis, descriptive analysis and path analysis. Based on the results of the study showed that 1) Based on the results of the path analysis showed that competence and work motivation had an impact on improving the work environment, this found the calculated F value of the competence and work motivation variable was 135,855, while the F table was 2.49. Thus fcount > ftable (135,855> 2.49), 2) Based on the results of the path analysis it shows that competence and work motivation have an impact on increasing work productivity. 49. Thus fcount > ftable (482,534>2.49). 3) Based on the results of the path analysis, it shows that the work environment has an impact on increasing work productivity, this is from the results of the t test for the work environment variable, it is obtained that t count = 15.765, and t table is 1.992. This means tcount > ttable (15.765 > 1.992). 4) Based on the results of the path analysis, it shows that competence and work motivation have an impact on increasing work productivity through the work environment, this is from the results X1 → X3 → Y = (ρx3x1) x (ρyx3) = 0.547 x 0.879 = 0.480, X2 → X3 → Y = (ρx3x2) x (ρyx3) = 0.357 x 0.879 = 0.313.